Rolverwagtinge van AGS-pastors: voorstelle vir 'n voortgesette teologiese opleidingsprogram - A. P. J. Putter; G. A. Lotter (Acta Theologica)
In this article, the focus will be on the findings of two qualitative research investigations of the role expectations of the Apostolic Faith Mission (hereafter AFM) pastor. It indicates the importance of a continuous theological training programme for the pastor. The necessity of equipping pastors to be more effective in their different role functioning poses an enormous challenge in these present days. Role players in the AFM and the broader church in general, as well as theological institutions face a major challenge, namely that of establishing relevant theological training, in order to help pastors become more effective in their different role expectations. A provisional model for a continuous theological training programme for the Ophir Network-pastor (at that time the South East Region of the AFM) will be discussed. The purpose of this article is to provide indications and guidelines for theological institutions towards a continuous theological training programme for pastors.